The Role of Product Quality, Brand Image, and Promotion on Purchasing Decisions of Best Meat in Pekanbaru - Riansyah, Putra Eldi; Sundari, Eva (Jurnal Manajemen Bisnis, 2024)
The meat industry, particularly in Pekanbaru, continues to thrive alongside changes in lifestyle and consumption patterns of the community. In this context, competition among service providers is intensifying, necessitating a deep understanding of factors influencing consumer purchasing decisions. This study aims to explore the influence of product quality, brand image, and promotion on consumer purchasing decisions at Best Meat, Pekanbaru. Best Meat is a well-known packaged meat brand in the archipelago, with one of its stores in Pekanbaru. In efforts to maintain and increase market share, Best Meat prioritizes aspects of halal certification, product quality, and commitment to renowned brands. This research employs a quantitative approach with direct or online surveys conducted among 171 consumers at the store. Data were collected through structured questionnaires covering inquiries about product quality, brand image, promotion, and purchasing decisions. The analysis results indicate that product quality, brand image, and promotion significantly influence consumer purchasing decisions. Regression coefficients for each variable show a positive relationship with purchasing decisions. Validity and reliability tests ensure the research instrument is valid and reliable. In conclusion, factors such as product quality, brand image, and promotion play a crucial role in influencing consumer purchasing decisions at Best Meat, Pekanbaru.